Financial Distress, Stock Returns, and the 1978 Bankruptcy Reform Act - Hackbarth, Dirk; Haselmann, Rainer; Schoenherr, David (Review of Financial Studies, 2015)
We study distress risk premia around a bankruptcy reform that shifts bargaining power in financial distress from debtholders to shareholders. We find that the reform reduces risk factor loadings and returns of distressed stocks. The reform effect is stronger for firms with lower firm-level shareholder bargaining power. An increase in credit spreads of riskier relative to safer firms, in particular for firms with lower firm-level shareholder bargaining power, confirms a shift in bargaining power from bondholders to shareholders. Out-of-sample tests reveal that a reversal of the reform's effect leads to a reversal of factor loadings and returns.